William A. Fetler in Exile, 1914–1957 - Raber, Mary (Journal of European Baptist Studies, 2021)
The Baptist preacher William A. Fetler (1883-1957) made important contributions to the evangelical movement in the Russian Empire and the Soviet Union, but most of his ministry was spent outside of that geographical area, following his exile in 1914. Besides surveying his many accomplishments in evangelism, literature production, and other ministries, this article focuses on Fetler’s identity as an exile and the ways that status may have shaped his activities.